Performance Comparison of Polycrystalline Solar Cells with and Without Reflectors - Septia Refly; Basyaruddin Ismail Harahap; Bimbi Aditya Wanatirta; Rahmat Kholis Harahap; Doli Bonardo (LPPM Universitas Negeri Semarang, 2025)
This research aims to analyze the comparison of power output between Polycrystalline solar panels with and without the use of mirror reflectors. The growing demand for sustainable energy sources necessitates ongoing efforts to enhance the efficiency of photovoltaic (PV) technology. In this study, a comparative experimental design was implemented over a two-day period, utilizing two identical solar panel configurations: a Reflector Equipped-Solar Panel (RESP) and a Solar Panel Without Reflector (WRSP). The electrical parameters of both configurations, including voltage, current, and power output, along with temperature, were continuously monitored and analyzed. The results indicate that the RESP consistently outperformed the WRSP. On average, the RESP produced 28–35% higher electrical current, which directly translated into a 25–32% increase in power output compared to the WRSP. The peak power of the RESP reached 21.3 W, whereas the WRSP peaked at 16.2 W. Although the RESP operated at a higher temperature (approximately 5–7 °C greater than WRSP), the power gain from increased irradiance effectively outweighed the thermal losses. These findings provide strong empirical evidence that reflective augmentation is a viable and cost-effective method for enhancing the performance of standard solar panels, offering valuable insights for maximizing renewable energy harvesting.